The Impact of Artificial Intelligence on Managing the Recruitment Process in a Company - Butryn, Beata; Rudnicki, Patryk (Wpływ sztucznej inteligencji na zarządzanie procesem rekrutacji w firmie, 2024)
Aim: The aim of this article is to analyse the impact of artificial intelligence on data management in the recruitment process in a company. Methodology: The method of document analysis was used, followed by an experiment, consisting in identifying artificial intelligence algorithms, preparing a data set, implementing algorithms, testing algorithms, and comparing the results – obtained from artificial intelligence algorithms in terms of efficiency, precision and speed of data processing, analysis and interpretation of the experiment results in the context of hypotheses and theories of data management and artificial intelligence. Results: Thanks to the use of the artificial intelligence algorithm, the efficiency of the recruitment process was increased by shortening its implementation time, and its effectiveness and quality were improved by a more objective and precise selection of suitable candidates. The integrity of the AI system with various advertising portals allowed for quick and easy posting of job offers on various platforms. The use of AI contributed to the reduction of costs and errors, which in effect leads to the sustainable development and success of the company. Implications and recommendations: The use of the AI algorithm allowed us to draw conclusions regarding the potential benefits and challenges related to the implementation of AI in data management. They can be a valuable guide for companies considering the implementation of AI in their structures, contributing to their development and improving operational and financial efficiency. Originality/value: The development of an algorithm for implementing AI technology in the recruitment process has shown tangible benefits resulting from its use.
Business Informatics = Informatyka Ekonomiczna, 2024, Nr 1-2 (67-68), s. 1-12
Keywords: artificial intelligence; machine learning; data management; recruitment process; sztuczna inteligencja; uczenie maszynowe; zarządzanie danymi; proces rekrutacji